A novel approach to non-invasive blood glucose sensing based on a single-slot defected ground structure. Issue 1 (22nd February 2023) - Mansour, Esraa; Allam, Ahmed; Abdel-Rahman, Adel B.
Abstract: In this study, we explore a novel approach to measure blood glucose concentration in a non-invasive way using a compact defected ground structure (DGS) filter. The proposed sensor is promising because it is cost-effective, compact, non-ionizing in nature, and convenient for diabetics. Therefore, a portable microwave biosensor can be utilized using these features. In this study, we present a single DGS sensor which is designed on a Rogers RO4003C substrate and fed by a 50 Ω microstrip line, and operating in the industrial, scientific, and medical radio bands (2.4–2.5 GHz). The changes in dielectric properties in blood are mainly relying on glucose concentrations. The main concept of using a sensor is by placing a finger on the sensing area (the slot). The filter is demonstrated by simulations using CST Microwave Studio. Additionally, the blood layer with different glucose concentrations from 250 to 16 000 mg/dl is presented by the Cole–Cole model. The sensor can achieve a relatively good sensitivity of 7.8285 kHz/mg/dl. The size of the fabricated sensor is 40 × 40 × 0.883 mm 3, which is suitable for hand-held use.